Environmental hotspots, frontiers and analytical framework of Blue Carbon research: a quantitative analysis of knowledge map based on CiteSpace - Zhang, Lipai (Frontiers in Environmental Science, 2024)
Blue Carbon is increasingly popular worldwide, and it also belongs to circular economy field which would last a long period in academy. To further understand the development and characteristics of Blue Carbon, this study uses CiteSpace software to perform quantitative analysis on literature published on Web of Science and Chinese CNKI database with the main topic of “Blue Carbon.” The results show that: (1) Since 2009, increasing attention has been paid to Blue Carbon research, among which the United States, Australia and China are the leading countries. (2) Keywords such as “Blue Carbon,” “mangrove,” “carbon sequestration” and “carbon neutrality” are the high-frequency keywords appearing both in China and the World in recent years. (3) Spartina alterniflora, soil organic carbon, livestock, trophic cascade, biodiversity and seagrass ecosystem clustering are hot topics related to international Blue Carbon research, while organic carbon, seagrass-conservation, methodology, sustainable development, climate change, carbon neutralization, coastal zone and carbon storage are hot topics related to Chinese Blue Carbon research. In addition, based on the research trends of Blue Carbon, this paper attempts to sort out the research framework from three levels: core characteristics, theoretical basis and research methods, respectively. Facing a series of challenges brought by climate change, Blue Carbon research should strengthen the accurate estimations of Blue Carbon sink and its market potential, and explore the reasonable market mechanism and protection mechanism, to respond to realistic demands, solve major concerns and promote new progress in Blue Carbon theory and practice.